PENGARUH PERUBAHAN TINGKAT PENGETAHUAN KESEHATAN GIGI DAN MULUT PADA PELAJAR USIA 7-8 TAHUN DI 2 SEKOLAH DASAR KECAMATAN MANDIANGIN KOTO SELAYAN KOTA BUKITTINGGI MELALUI PERMAINAN EDUKASI KEDOKTERAN GIGI - Dedi Sumantri; Yuniar Lestari; Mustika Arini (Andalas Dental Journal, 2013)
The prevalence of caries among school children in West Sumatera is still high. Dental health education is important in order to increase dental health status in children because of that the development of a new strategy in dental health education is needed. One of the way is by using game, because children usually like that media. This study was aimed to find out the effectiveness of dental education game by using snake and ladder as the media in changing 7-8years old student’s knowledge about teeth and mouth. The method of this study was analytic experimental with non equivalent pre and post test control group design. Fourty one student's with 7-8 years old of two Elementary Schools ( 17 Manggis Ganting and 03 Pulai Anak Air elementary school ) were used as the study sample of experiment group, this group was given dental education games method with snake and ladder games as the media and fourty one student's with 7-8 years old of 17 Manggis Ganting and 03 Pulai Anak Air elementary school were used as the control group where in this group was given nothing. Analysis of data was using Paired Samples T-Test and Independent Samples T-Test based on 0,05 as significant. The pretest and posttest analysis of knowledge showed that mean percentage of experiment group is 13,32% ±12,475 and 4,44% ±11,713 for the control group. Both of groups have significant difference where p=0,00(p<0,05). Dental education games method with snake and ladder games as media was effective in increasing student’s knowledge in comparing with the control group. So in order to increase dental health knowledge, dental education games could be use as one of dental education method for 7-8 years old students.